In vitro and in vivo anti-inflammatory activity of 17-O-acetylacuminolide through the inhibition of cytokines, NF-κB translocation and IKKβ activity - Achoui, Mouna; Appleton, David; Abdulla, Mahmood Ameen; Awang, Khalijah; Mohd, Mustafa Ali; Mustafa, Mohd Rais (Public Library of Science, 2010)
BACKGROUND AND PURPOSE: 17-O-acetylacuminolide (AA), a diterpenoid labdane, was isolated for the first time from the plant species Neouvaria foetida. The anti-inflammatory effects of this compound were studied both in vitro and in vivo.